Methodology in Setting-Up a Three-Dimensional Flow Model for the Strait of Malacca, Malaysia - Ramadhan Basiddiq, Ramadhan Ahmed; Abdul Rahman, Anas; Abdul-Rahman, Ayu; Rosli, Azzim; Marzuki, Najwa Syafiqa; Wan Zulkafli, Wan Muhammad Fadhli Arif; Misran, Mohamad Syahfiq (Journal of Advanced Mechanical Engineering Applications, 2022)
As a rapidly developing and expanding country, Malaysia is expected to see an increase in its electricity consumption in the near future. Although known for its abundance of natural resources, specifically petroleum and natural gas, Malaysia has pledged to reduce its dependency on conventional resources and aims to become a carbon-neutral nation by the year 2050. This can be achieved by unlocking sustainable alternatives from the ocean, such as waves and tidal current energy, which are known to be abundant, continuous, and clean. Although various studies had identified several locations along the Straits of Malacca with potential to be used as deployment sites for tidal stream turbines, most of them were focused only on theoretical resource assessment. Since detailed three-dimensional flow models for the Malacca Strait have yet to be thoroughly developed, examined, and discussed, this study aims to provide a preliminary methodology for setting up a three-dimensional numerical model for this region. The analysis of the study consists of three steps: pre-processing using Blue Kenue; processing with Telemac 3D; and post-processing, which visualizes the simulation outcome. The output from the simulation is validated against published measurement data to ensure the accuracy and robustness of the numerical model. The simulation outcome reveals that the southeast part of the Malacca Strait could be a promising area for deploying tidal stream turbines due to the high tidal current velocity in that area. Additionally, it is also observed that the kinetic energy flux increases towards the southeast part of the strait due to the strait's narrow size in that area. Overall, a detailed procedure for setting up a three-dimensional flow model for the Strait of Malacca is presented, and it is hoped that this work could highlight some of the complexity involved in developing an ocean-scale model for this region.